2013
DOI: 10.1186/bcr3404
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia virus GLV-1h153 is a novel agent for detection and effective local control of positive surgical margins for breast cancer

Abstract: IntroductionSurgery is currently the definitive treatment for early-stage breast cancer. However, the rate of positive surgical margins remains unacceptably high. The human sodium iodide symporter (hNIS) is a naturally occurring protein in human thyroid tissue, which enables cells to concentrate radionuclides. The hNIS has been exploited to image and treat thyroid cancer. We therefore investigated the potential of a novel oncolytic vaccinia virus GLV1h-153 engineered to express the hNIS gene for identifying po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…VV carrying NIS was used as an imaging tool to identify positive surgical margins of breast cancer in a murine model (150). Ninety percent of the tumors xenografted into the mammary fat pad were surgically resected and subsequently injected with VV-NIS in the surgical wound.…”
Section: Replication-competent Oncolytic Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…VV carrying NIS was used as an imaging tool to identify positive surgical margins of breast cancer in a murine model (150). Ninety percent of the tumors xenografted into the mammary fat pad were surgically resected and subsequently injected with VV-NIS in the surgical wound.…”
Section: Replication-competent Oncolytic Virusesmentioning
confidence: 99%
“…Ninety percent of the tumors xenografted into the mammary fat pad were surgically resected and subsequently injected with VV-NIS in the surgical wound. 124 I − microPET images showed that fewer than 10% of cells were still alive five days after treatment (150). VV carrying NIS was also successfully used in a combined therapy with radionuclides, exploiting the induced capability of the infected cells to actively accumulate 131 I − , as reported by Gholami et al (151) for anaplastic thyroid tumors that had lost their ability to accumulate I − and by Mansfield et al (152) for prostate cancer.…”
Section: Replication-competent Oncolytic Virusesmentioning
confidence: 99%
“…Fluorescent imaging can assist clinicians by detecting viral distribution in order to monitor therapeutic effects via tumor localization and drug toxicity. Our laboratory has previously shown that this viral reporter gene may be utilized as a predictor of response to therapy [10] and to monitor invasion and metastatic spread in TNBC cells [11]. Lastly, we note that oncolytic vaccinia therapy is a safe approach as it has been demonstrated to be safely given to millions of patients during the smallpox eradication.…”
Section: Discussionmentioning
confidence: 95%
“…In our laboratory, we have previously shown that vaccinia virus can infect, replicate in, and kill cancer cells, including anaplastic thyroid [7], pancreatic [8], gliomas [9], and breast [10], specifically including TNBC [11]. GLV-1h164 is an oncolytic vaccinia virus strain that contains the single-chain antibody sequence for GLAF-2, an antibody directed against VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…GLV-1h164 was generated using an scAb for VEGF to suppress VEGF activity, and its efficacy was tested in TNBC cell lines and an orthotopic murine model. 55 The therapeutic efficacy of GLV-1h153 that expresses NIS was also evaluated in prostate cancer models as different combinations with external beam radiotherapy and NIS-mediated radioiodine therapy. Human prostate cancer cell lines -PC3, DU145, LNCaP, and WPMY-1 were used as in vitro models.…”
Section: Vv Replicationmentioning
confidence: 99%